An Experimental Pilot Approach to Evaluate the Infrastructure Accessibility and Level of Service at Metro Station Platforms - Sebastian Seriani; Vicente Aprigliano; Alvaro Peña; Shirley Gonzalez; Bernardo Arredondo; Iván Bastías; Emilio Bustos; Jose Requesens; Ariel Lopez; Taku Fujiyama (Applied Sciences, 2025)
Metro stations are essential for daily commuting, but overcrowding due to increased demand can severely impact infrastructure quality and passenger experience. The Level of Service (LOS), a key indicator of congestion, is influenced by factors such as density, flow, and speed, and poor LOS leads to issues like longer boarding times, overcrowded platforms, and reduced accessibility, especially for vulnerable populations. To address these challenges, the study explores innovative solutions to improve platform design infrastructure for better accessibility and LOS, aligning sustainable development goals to create safer, more inclusive transport systems. This study presents two strategies designed to reduce passenger congestion at Francia station on the Valparaíso metro platform infrastructures. The strategies, tested in experimental scenarios, showed minimal differences in boarding and alighting times, with less than a one-second average variation between the two. However, survey results revealed that passengers preferred the strategy “let passengers alight before boarding the train”, as it provided greater comfort and accessibility, reducing the number of passengers per door and improving the LOS from level C to B. Despite the minimal intervention in the experiments, the results suggest potential operational improvements. Future research will focus on measuring passengers’ emotional responses using psychophysiological data to further evaluate the suitability of the proposed strategies.